To Protect or Not to Protect- Tariffs in Small Countries: Evidence From Egypt - Bakeer, Mayar; Ghoneim, Hebatallah (Journal of Applied Business and Economics, 2021)
In a world promoting free trade, policies aim to increase economic welfare. Nevertheless, the impact of decreasing protectionism on small countries has been unclear. The aim of this research is to evaluate the effect of decreasing tariff rates on welfare in small developing countries, using Egypt as a case study. This is done through simulating the tariff rates imposed by the Egypt-European Union Association Agreement (E-EUAA), which calls for tariff rates to be gradually decreased until they reach zero. The results show that the lower the protectionism, the lower the welfare, which is attributed to low export levels within the country and high prices.